Three Basic Skills of Rectilinear Motion Chart Interpretation; What Do Students Already Have and How Should They Be? Tiga Keterampilan Dasar Interpretasi Grafik Gerak Lurus; Apa yang Sudah Siswa Miliki dan Bagaimana Seharusnya? - Putri, Rizqy Nur Ayu; Sutopo, Sutopo (SEJ (Science Education Journal), 2024)
This study focuses on identifying high school students' skills in interpreting kinematics graphs of linear motion. The research was implemented by quantitative method to 70 students. The data collection technique was carried out by giving a direct test of 26 multiple choice questions adopted from TUG-K. The students' skills identification was reviewed based on three basic graphing skills, the results showed that 39% of students were skilled in reading graphs directly, 47% of students were skilled in interpreting the slope/gradient of the line and 37% of students were skilled in interpreting the area under the curve. This study found that students did not have full graphing skills. In the case of transforming one graph to another that requires a combination of two or more basic skills, the percentage success score decreased, 37% in the combination of basic skills 1-2 and 31% in the combination of 1-3. The combination of basic skills that requires a more complex thinking process is the main reason for students' failure to answer the questions correctly. The results of this study can be the basis of information for further research in improving students' skills in linear motion graphs.